Simon Gathercole, The Gospel of Thomas: Introduction and Commentary (Texts and Editions for New Testament Study 11; Leiden – Boston: Brill 2014) - Oracz, Anna (The Biblical Annals, 2016)
Book review: Simon Gathercole, The Gospel of Thomas: Introduction and Commentary (Texts and Editions for New Testament Study 11; Leiden – Boston: Brill 2014). Pp. 723. € 193.00. US$ 250.00. ISBN 978-90-04-19041-2.